The Effect of Price, Ease of Transaction, Information Quality, Safety, and Trust on Online Purchase Decision - Rizqi Maulana Ilham Akbar; Raden Andi Sularso; Ketut Indraningrat (e-Journal Ekonomi Bisnis dan Akuntansi, 2020)
This research aims to analyze the effect of price, ease of transaction, information quality, safety, and trust on online purchase decision. Applying purposive sampling technique, the sample was students of the Department of Management, Faculty of Economics and Business, University of Jember that consisted of 100 respondents. This study used quantitative data sourced from primary data. Data were analyzed using multiple linear regression. Results showed that, both partially and simultaneously, the variables of price, ease, information quality, safety, and trust had a significant positive effect on online purchase decision.